An adaptive fuzzy sliding mode controller for the depth control of an underactuated underwater vehicle. (10th April 2019) - Chen, Yuan; Yan, Yinpo; Wang, Kangling; Liu, Shuqi
An adaptive fuzzy sliding mode controller is proposed for the depth control of an underactuated underwater vehicle based on the state-dependent Riccati equation. An adaptive fuzzy control algorithm is embedded into the sliding mode controller to solve the buffering and mismatched uncertain problems in the robust sliding mode variable structure controller, where an auxiliary fuzzy control unit is designed to automatically adjust the scale factor of the main fuzzy controller output. Based on Lyapunov stability theory and final value bounded theorem, the stability and convergence properties of the closed-loop system are demonstrated. Numerical simulations are carried out to validate the effectiveness of the proposed controller.